Proposed new interior design of HPA Beauty Spa and Academy for HPA Sdn. Bhd. at C-G- 1, Greentown Suria, Jalan Dato Seri Ahmad Said, 30450 Ipoh, Perak / Nabilah Mansor - Mansor, Nabilah (Faculty of Architecture, Planning and Surveying, 2010)
The project that had been chosen for the final project is to Proposed New Interior Design for the interior and appeals the corporate image of HPA Beauty Spa and Academy. This proposed spa academy is to attract clients, mostly on businesswomen who trying to have their own business, and provide the better facilities. As a designer, to solve problems can be done by doing a literature review. The objective of this propose spa is to have different and unique spa in Malaysia, to have an ergonomic design that has a good flow and allow for easy access between client and staff. By doing the research methodology, all data information have gather to obtained and finalize the design form to propose the new interior design for spa and academy. Conclusion, this propose spa and academy is to be one of the leading spa in the Malaysia region to appeal to the senses and promote an inner sense of well-being.